KAJIAN PEMANFAATAN DATA GOOGLE MAPS DALAM OFFICIAL STATISTICS - Cholifa Fitri Annisa; Setia Pramana (Seminar Nasional Official Statistics, 2020)
Publication of food and drink supply business statistics published by BPS cannot facilitate businessmen in identifying areas that have the potential to develop businesses in the food and drink supply sector. In addition, there are limitations in time, cost, and manpower in data collection by the BPS Tourism Sub-directorate on the VREST survey, so that the food and drink supply statistics cannot be published according to the methodology, namely every year. This study utilizes the web scraping method to obtain business data on food and drink providers from the google maps website. The amount of data collected is as many as 34,526 food and drink providers in Java and Bali. The results of the matching value of web scraping data with BPS data frames show a match percentage of 68.22%. Bali Province is an area that has the potential to develop food and beverage supply businesses, especially in the City / Regency of Jembrana, Buleleng, Tabanan, Karangasem, and Klungkung. Meanwhile, Central Java province is an area that has the potential to develop accommodation businesses, especially in the cities / regencies of Cilacap, Blora, Grobogan, Batang, and Kendal.